THE EFFECT OF ENGLISH SONGS IN ENRICHING VOCABULARY TO EIGHTH GRADE STUDENTS OF SMP NEGERI 8 SATAP TONDANO - Felicia, Vania; Mogea, Tini; Olii, Sanerita (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research aims to find a significant effect of English songs in enriching students’ vocabulary mastery at SMP Negeri 8 Satap Tondano. This research used quantitative method with pre-experimental design, specifically the onegroup pre-test and post-test. The sample of this research is 8th grade students which consist of 19 students. The steps in data collection used in this research are: pre test, conducted to measure the students’ initial vocabulary mastery, then treatment, conducted in two meetings to enrich the vocabulary of the students, and lastly post test, conducted to measure the students’ vocabulary mastery after implementing English songs in language learning. Based on the data, students acquired insufficient grades on the pre-test or before receiving treatment. Students’ grades were significantly higher on the post-test or after treatment compared to the pre-test. The mean score on pre test was 66,36 and on the post test was 83,36. For the significance level (P = 0.05), df = 18, with the value of the t test is 25.75, and the value of the t table is 2.101, it can be seen that the value of the t test is greater than the t table, or t test ≥ t table (25.75 ≥ 2.101). Based on the findings, it can be concluded that there was a significant effect of English songs in enriching students’ vocabulary mastery.